Prasugrel Compared With High Loading- and Maintenance-Dose Clopidogrel in Patients With Planned Percutaneous Coronary Intervention: The Prasugrel in Comparison to Clopidogrel for Inhibition of Platelet Activation and Aggregation–Thrombolysis in Myocardial Infarction 44 Trial - Wiviott, Stephen D.; Trenk, Dietmar; Frelinger, Andrew L.; O’Donoghue, Michelle; Neumann, Franz-Josef; Michelson, Alan D.; Angiolillo, Dominick J.; Hod, Hanoch; Montalescot, Gilles; Miller, Debra L.; Jakubowski, Joseph A.; Cairns, Richard; et al. (Circulation (New York, N.Y.), 2007)
Background— The increasing use of higher-than-approved doses of clopidogrel in clinical practice is based in part on the desire for greater levels of inhibition of platelet aggregation (IPA). Prasugrel is a new thienopyridine that is more potent than standard-dose clopidogrel in healthy subjects and patients with stable coronary artery disease. The relative antiplatelet effects of prasugrel versus high-dose clopidogrel in percutaneous coronary intervention patients are unknown. Methods and Results— Prasugrel in Comparison to Clopidogrel for Inhibition of Platelet Activation and Aggregation–Thrombolysis in Myocardial Infarction 44 (PRINCIPLE-TIMI 44) was a randomized, double-blind, 2-phase crossover study of prasugrel compared with high-dose clopidogrel in patients undergoing cardiac catheterization for planned percutaneous coronary intervention. The primary end point of the loading-dose phase (prasugrel 60 mg versus clopidogrel 600 mg) was IPA with 20 μmol/L ADP at 6 hours. Patients with percutaneous coronary intervention entered the maintenance-dose phase, a 28-day crossover comparison of prasugrel 10 mg/d versus clopidogrel 150 mg/d with a primary end point of IPA after 14 days of either drug. In this study, 201 subjects were randomized. IPA at 6 hours was significantly higher in subjects receiving prasugrel (mean±SD, 74.8±13.0%) compared with clopidogrel (31.8±21.1%; P <0.0001). During the maintenance-dose phase, IPA with 20 μmol/L ADP was higher in subjects receiving prasugrel (61.3±17.8%) compared with clopidogrel (46.1±21.3%; P <0.0001). Results were consistent across all key secondary end points; significant differences emerged by 30 minutes and persisted across all time points. Conclusions— Among patients undergoing cardiac catheterization with planned percutaneous coronary intervention, loading with 60 mg prasugrel resulted in greater platelet inhibition than a 600-mg clopidogrel loading dose. Maintenance therapy with prasugrel 10 mg/d resulted in a greater antiplatelet effect than 150 mg/d clopidogrel.